A Geografia Atual: A Objetividade Dada A Geografia a Construir: A Objetividade a Vir-a-Ser (Formação (Online), 2012)
A Geografia Atual: A Objetividade DadaA Geografia a Construir: A Objetividade a Vir-a-Ser